2017
DOI: 10.1111/obr.12489
|View full text |Cite
|
Sign up to set email alerts
|

Maternal body mass index and post‐term birth: a systematic review and meta‐analysis

Abstract: SummaryPost‐term birth is a preventable cause of perinatal mortality and severe morbidity. This review examined the association between maternal body mass index (BMI) and post‐term birth at ≥42 and ≥41 weeks' gestation. Five databases, reference lists and citations were searched from May to November 2015. Observational studies published in English since 1990 were included. Linear and nonlinear dose–response meta‐analyses were conducted by using random effects models. Sensitivity analyses assessed robustness of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 78 publications
1
33
2
Order By: Relevance
“…In their recent review and meta‐analysis, Heslehurst et al . also found that in order to minimize bias, it was essential to include evidence from searches in addition to database searching .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In their recent review and meta‐analysis, Heslehurst et al . also found that in order to minimize bias, it was essential to include evidence from searches in addition to database searching .…”
Section: Discussionmentioning
confidence: 99%
“…Of the 22 included studies, 20 were identified through database search alone (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(42)(43)(44)(45)(46)48), one from screening the reference lists of relevant reviews (41) and one from searching the citations of included studies (47). In their recent review and meta-analysis, Heslehurst et al also found that in order to minimize bias, it was essential to include evidence from searches in addition to database searching (7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BMI is a significant predictor of maternal and perinatal health outcomes. For example, there is an increased risk of maternal and perinatal mortality, gestational diabetes, pre-eclampsia, pre- and post-term birth, stillbirth and congenital anomalies when mothers have a BMI in the overweight or obese ranges compared with women who have a BMI in the recommended range [ 7 , 14 – 19 ]. There are also increased risks for mothers with an underweight BMI, including preterm birth and miscarriage [ 20 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The multivariable linear regression model included the potential confounders maternal age and parity 19 . In addition, estimates were adjusted for the mediators gestational age and mode of delivery 20‐22 . An erythropoietin concentration ≥60 U/L was considered as high.…”
Section: Methodsmentioning
confidence: 99%